1993
DOI: 10.1021/ja00079a039
|View full text |Cite
|
Sign up to set email alerts
|

De novo design and synthesis of somatostatin non-peptide peptidomimetics utilizing .beta.-D-glucose as a novel scaffolding

Abstract: Non-peptide peptidomimetics of the peptide hormone somatostatin (SRIF) were designed and synthesized, utilizing fl-D-glUCOSe as a novel scaffolding. Such compounds resemble conventional peptide analogs in that they retain critical amino acid side chains but differ in that they are devoid of both the peptide backbone and amide surrogates. Structure-activity relationships resulting from systematic deletion or modification of the side chains of 4a were consistent with expectations, with the exception that analogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(123 citation statements)
references
References 0 publications
2
121
0
Order By: Relevance
“…Thus, the carbohydrate scaffold can display substituents to control distance and geometry between them. In this context, Hirschmann et al 9,12 and Nicoloau et al 13 described nonpeptidal peptidomimetics with novel scaffolding. Already in 1977, Walter 14 had suggested that backbone amide elements may not be required for receptor interaction and that a cyclic scaffold could be used.…”
Section: Peptidomimetics: Configurational and Conformational Propertimentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the carbohydrate scaffold can display substituents to control distance and geometry between them. In this context, Hirschmann et al 9,12 and Nicoloau et al 13 described nonpeptidal peptidomimetics with novel scaffolding. Already in 1977, Walter 14 had suggested that backbone amide elements may not be required for receptor interaction and that a cyclic scaffold could be used.…”
Section: Peptidomimetics: Configurational and Conformational Propertimentioning
confidence: 99%
“…Already in 1977, Walter 14 had suggested that backbone amide elements may not be required for receptor interaction and that a cyclic scaffold could be used. Scaffolding had been used and proven in the 1980s, when Hirschmann et al 9,12 and Nicoloau et al 13 described an approach to design of peptidomimetics, wherein the entire amide backbone of a -turn is replaced by novel scaffoldings devoid of amide bonds or isosteric replacements (described in more detail in the section Carbohydrates as Scaffolds in the Design of Nonpeptide Peptidomimetics of Somatostatin).…”
Section: Peptidomimetics: Configurational and Conformational Propertimentioning
confidence: 99%
See 1 more Smart Citation
“…The elucidation of the 3-dimensional structures of receptor subtype-selective somatostatin agonists has aided and will considerably enhance the rational design of novel analogs including non-peptide compounds [135][136][137]. Development of potent non-peptide somatostatin analogs is important because they may display a good bioavailabilty [138] following oral administration.…”
Section: New Somatostatin Analogs and Regimensmentioning
confidence: 99%
“…Specificity of a small molecule for an individual protein family member may be overlayed on a common scaffold by groups that provide specific binding interactions (hydrophobic bonds, salt bridges, hydrogen bonds, etc.). For example, scaffolds designed to interact with an important family of signal transducing molecules, G-protein-linked receptors, provide an approach to a novel set of potentially selective ligands (47) (Fig. 4).…”
Section: Selecting Sources To Be Screened For Drugs and Leadsmentioning
confidence: 99%